Structure and phase transition peculiarities in solid nitrous oxide and attempts at their explaination - Drobyshev, A.; Aldiyarov, A.; Korshikov, E.; Kurnosov, V.; Sokolov, D.; Tokmoldin, N. (Физика низких температур, 2013)
Cryogenic vacuum deposited films of nitrous oxide were studied at the following conditions: a mirror-like silver-coated copper substrate; deposition temperature 16 K; gas phase pressure during deposition 10⁻³ Pa. Anal-ysis of the IR-spectrometric and thermodesorption data leads to the following conclusion. The transition from the amorphous to crystalline state in the vicinity of 40 K proceeds in several steps which reflect relaxation processes related to different molecular vibrations. The differences in the temperature intervals of the transitions are de-termined by the activation energies of relevant vibrations. It was shown that cryocondensation at 16 K is accom-panied by appearance of flashes on the condensate surface. Based on the uniform nature of the observed processes, a model based on several possible isomorphic molecular states of nitrous oxide is suggested.